A Multigroup Structural Equation Model of Family Functioning, Identity Development, and Risk-Taking Behaviors among Adolescents - Escalante, Verónica; Desrosiers, Liam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
The present study aimed to examine the structural relationships among family functioning, identity development, and risk-taking behaviors among Canadian adolescents and to determine whether these relationships differ between male and female adolescents using a multigroup structural equation modeling approach.Methods and Materials: This cross-sectional correlational study was conducted among 842 adolescents aged 14–18 years recruited from secondary schools in Ontario, British Columbia, and Alberta, Canada. The sample consisted of 421 males and 421 females selected through multistage cluster sampling. Data were collected using the Family Assessment Device (FAD), the Dimensions of Identity Development Scale (DIDS), and the Adolescent Risk-Taking Questionnaire (ARQ). Descriptive statistics, reliability analyses, confirmatory factor analysis, and structural equation modeling were performed using SPSS 29 and AMOS 29. Multigroup structural equation modeling was employed to examine the invariance of the proposed model across gender groups. Model fit was evaluated using χ²/df, Comparative Fit Index (CFI), Tucker–Lewis Index (TLI), Goodness-of-Fit Index (GFI), Incremental Fit Index (IFI), and Root Mean Square Error of Approximation (RMSEA). Direct, indirect, and total effects were estimated, and mediation effects were tested using bias-corrected bootstrap procedures with 5,000 resamples.Findings: The measurement model demonstrated excellent fit to the data (χ²/df = 2.10, CFI = .961, TLI = .957, RMSEA = .036). Structural equation modeling revealed that family functioning positively predicted identity development (β = .62, p < .001), while identity development negatively predicted risk-taking behaviors (β = -.56, p < .001). Family functioning also exerted a significant direct negative effect on risk-taking behaviors (β = -.31, p < .001). Bootstrap analyses confirmed a significant indirect effect of family functioning on risk-taking behaviors through identity development (β = -.35, p < .001), indicating partial mediation. The model explained 38% of the variance in identity development and 54% of the variance in risk-taking behaviors. Multigroup analyses supported configural, metric, scalar, and structural invariance across male and female adolescents, indicating that the proposed relationships operated similarly across gender groups.Conclusion: The findings demonstrate that family functioning is a significant protective factor against adolescent risk-taking behaviors both directly and indirectly through its positive influence on identity development. Adolescents who experience supportive, cohesive, and effectively functioning family environments are more likely to develop stable and adaptive identities, which in turn reduces their likelihood of engaging in maladaptive risk behaviors. The invariance of the model across genders suggests that these developmental processes are broadly consistent for male and female adolescents. These findings highlight the importance of family-centered and identity-focused interventions in promoting healthy adolescent development and preventing behavioral risk outcomes.